Determination of optimum geothermal Rankine cycle parameters utilizing coaxial heat exchanger. (1st May 2016) - Mokhtari, Hamid; Hadiannasab, Hasti; Mostafavi, Mostafa; Ahmadibeni, Ali; Shahriari, Behrooz
Abstract: The main objective of this study is determining the optimal parameters of geothermal Rankine cycle using coaxial heat exchanger from 4 viewpoints: (1) First law of thermodynamics (2) Working fluid (3) Second law of thermodynamics and (4) Costs. Optimization of diameter ratio was accomplished with respect to pressure drop decrement inside the heat exchanger and cycle thermal efficiency increment. Optimal values for diameter ratio were determined to be 0.675 and 0.353 for pressure drop minimization and thermal efficiency maximization, respectively. The Organic Rankine Cycle which uses water as intermediate fluid was assessed regarding to the optimum values of diameter ratio from energy, exergy and exergo-economic standpoints. The analysis led to exergy destruction cost estimation. The amount of exergy destruction cost was added to the cycle cost function which includes the cost of purchasing, maintenance and piping. To specify the best working fluid for the power cycle, a comparison was made between four different organic fluids and water based on power generation and costs. Finally, R123 was detected as the most appropriate working fluid. For obtaining an optimum system, two standpoints were still remained which should be considered and they are cost and exergy efficiency. These parameters were optimized while the thermal efficiency constraint had been set to its optimal value (for 0.353 as diameter ratio). As a result, optimum values for cycle parameters were met. These parameters are pressure and temperature of main organic fluid and the condenser pressure. For coaxial heat exchanger, the optimized parameters are input water velocity, output steam pressure and outer diameter. Highlights: Find the optimal diameter ratio to increase the efficiency of geothermal cycle. Calculation of the exergy destruction cost in the cost function of the cycle. Optimization of cycle parameters according to the optimum working fluid. Thermal modeling and exergy analysis of double pipe heat exchangers.